Decision-making model for choosing residential building repair variants - Bucoń, Robert; Sobotka, Anna (Journal of Civil Engineering and Management, 2015)
During the use of buildings it becomes necessary to carry out repair works including modernisation. Deciding on the choice of repair solutions is a difficult and complex task. Building administrators have to consider both, the benefits of some repair works, and limitations due to the availability of funds. Selection of a repair solution, bearing in mind the above, requires a comprehensive approach that will allow assessment of the building condition and determining the repair scope required. The research conducted by the authors was aimed at developing a decision-making model and its computer-aided implementation, taking into account a number of operating demands. The system algorithm proposed comprises five stages including: building condition assessment, building use value evaluation, repair classification, multiple variants of repair and the choice of repair solutions. The article describes individual stages of the model in detail, giving numerical application examples of the method for repair solution choice for five multi-family houses.